Characterisation of low-odour emissive polylactide/cellulose fibre biocomposites for car interior - D. Rusu; C. Courgneau; C. Henneuse; V. Ducruet; M-F. Lacrampe; P. Krawczak (eXPRESS Polymer Letters)
Low odour-emissive polylactide/cellulose fibre biocomposites, intended for car interior, were prepared and characterised. The impact of the different stages of processing (drying cycles, compounding, injection moulding) on the extent of polylactide degradation and on biocomposites properties was investigated by size exclusion chromatography, thermogravimetry, differential scanning calorimetry. In parallel, the odour emission of these materials was quantified via dynamic dilution olfactometry and Field of odours® method. The changes in molecular weight and global odour emission indicated that compounding had a strong impact on polylactide degradation and odour emission, while injection moulding had no significant impact. Adding 0.5 wt% of an absorbent agent based on poly(1-methylpyrrol-2-ylsquaraine could) divide the global odour concentration by a factor 2. The morphology, mechanical and thermal properties of injection moulded PLAbiocomposites were not affected by the presence of the absorbent agent.